1983
DOI: 10.1113/jphysiol.1983.sp014509
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and action of a disulphonic stilbene (SITS) in the perfused guinea‐pig liver: a comparison with bromsulphthalein.

Abstract: SUMMARY1. Livers were perfused with a Krebs-Ringer bicarbonate buffer in a single-pass perfusion system. Bile secretion was maintained by infusion of secretin. 4-Acetamido-4'-isothiocyano-2,2'-stilbene disulphonic acid (SITS) was added to the perfusate to give concentrations ranging between 5 x 10-6 and 10-4 M.2. SITS was extracted from the perfusate by the liver (V, 0 15 ,tmol/min per g liver; Km 8X6 x 10-5 M) and excreted in bile in a modified form (bile/plasma ratio: 50-170; maximum rate of excretion: 25 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Although we found inhibition of BSP uptake by DIDS pretreatment of cultured hepatocytes, it is not clear whether this represents inhibition of a Clchannel or direct inhibition of the organic anion transport mechanism. In the rat, the related compound 4-acetamido-4'-isothiocyano-2,2'-stilbene disulfonic acid has been found to be transported intact into bile (40). The present studies are consistent with bidirectional hepatic organic anion transport in exchange for Cl-or NO-, similar to mechanisms described in kidney and intestine.…”
Section: Discussionsupporting
confidence: 86%
“…Although we found inhibition of BSP uptake by DIDS pretreatment of cultured hepatocytes, it is not clear whether this represents inhibition of a Clchannel or direct inhibition of the organic anion transport mechanism. In the rat, the related compound 4-acetamido-4'-isothiocyano-2,2'-stilbene disulfonic acid has been found to be transported intact into bile (40). The present studies are consistent with bidirectional hepatic organic anion transport in exchange for Cl-or NO-, similar to mechanisms described in kidney and intestine.…”
Section: Discussionsupporting
confidence: 86%
“…(i) While substrates of Na+-dependent bile acid transport were ineffective, BSP competitively inhibited hyperpolarization of membrane voltages; the K1 of (0 5 mM) BSP in this process was 50 AM, which is in good agreement with Km values of BSP uptake of rat liver in situ (46 /sM; Scharschmidt et al 1975) and of isolated perfused guinea-pig liver (18 /M; Rutishauser, 1983). (ii) Cl-substitution by gluconate decreased the rate of voltage changes by some 45 %, which exactly matches the decrease of [35S]BSP uptake by short-term cultured rat hepatocytes (Min et al 1991) and isolated perfused rat liver (Wolkoff et al 1987).…”
Section: Fluorimetric Determination Of Dids Uptakesupporting
confidence: 65%
“…In isolated perfused rat liver, DIDS is taken up and secreted into bile (Anwer, Nolan & Hardison, 1988). In guinea-pig liver, SITS is transported into bile at rates comparable to those of BSP secretion (Rutishauser, 1983). If DIDS is transported into liver cells and modifies membrane (K+) conductance from the inside, substrates of hepatocyte anion transport should interfere with membrane hyperpolarization.…”
Section: Microfluorimetrymentioning
confidence: 99%
“…12). Furthermore DIDS (Anwer et al 1988) and SITS (Rutishauser 1983) themselves have been reported to be secreted against a concentration gradient into bile. One might wonder about the specificity of compounds such as DIDS and NAP taurine for organic anion transport systems since both compounds interfere with several anion permeation pathways (Aronson 1989).…”
Section: Hepatocellular Uptake Of Cysteine Sulfinate and Taurinementioning
confidence: 99%